URGENSI PEMAHAMAN HADIS KONTEKSTUAL - Lailiyatun Nafisah (IAIN Kediri, 2019)
This paper explains the way or method in understanding hadith. Hadith is the second Muslims guidance after the Qur’an. In it capacity, believed that hadith is answers of society problems. But hadith is the remaining text, however, the problems that occur in society are continuing to develop. So it is not uncommon to find the hadith text that appears to contradict current conditions. To face this problem, it necessary to formulate new methods and approaches to understand the hadith. One of them is the contextual understanding method. Through this method hadith can be understood properly and correctly based on the needs and current condition. But it must be admitted that not all of hadith can be contextualizedKeywords: Text, Understanding, Contextual, Hadith